MycoNews 2021: President’s message, IMA statutes, news, reports, awards, personalia, and book news - David L. Hawksworth (IMA Fungus)
Abstract This third annual edition of MycoNews starts with a message from IMA President Wieland Meyer regarding the adoption of new statutes for the IMA, the postponement of IMC12 to 2024, and announcing Marc Stadler as President-elect. The new statutes are included in full. News is provided on the launch of a World Fungus Day, acceptance of the term Funga as an equivalent to Fauna and Flora by the IUCN Species Survival Commission, new arrangements and dates for IMC12 now to be held in Maastricht in July 2024, and revised arrangements for the publication of proposals to change any rules governing the nomenclature of fungi. Reports are provided for IAL9, the symposium of the International Association for Lichenology in Brazil mainly conducted virtually, MycoRise Up! in Poland, and the centenary of the German Mycological Society (DGFM). Birthday greetings from IMA go to David Farr, Marie-Agnés Letrouit-Galinou, Maria Olech, Angela Restrepo, Carol Shearer, James Trappe, and Shun-ichi Udagawa. Tributes are also paid to the passing of the distinguished mycologists Heinz Butin, Karl Esser, Grégoire Hennebert, Jack Rogers, Kálman Vánky, and Bodo Wanke. The contribution concludes with news of seven new mycological books published in 2020–2021, and another forthcoming in 2022.